2010
DOI: 10.1227/01.neu.0000369607.71913.3e
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy for Elevated Intracranial Pressure and Its Effect on the Cumulative Ischemic Burden and Therapeutic Intensity Levels After Severe Traumatic Brain Injury

Abstract: These results suggest that a DC for increased ICP can reduce the CIB of the brain after severe TBI. We suggest that DC be considered early in a patient's clinical course, particularly when the TIL and ICP are increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 61 publications
1
49
0
1
Order By: Relevance
“…Intracranial hemorrhage and midline shift are also indications of increased intracranial pressure. When coupled with vascular compression and secondary cerebral infarction, severe brain edema may occur, which may lead to a significant increase in intracranial pressure (8,25,31). A less severe injury may lead to small-scale single-focal intracranial hematoma associated with less severe postoperative cerebral edema, whereas more traumatic injury often results in multi-focal complex hematoma, which is associated with more severe cerebral edema and increased intracranial pressure (4).…”
Section: Wang X Et Al: Bone Flap Of Traumatic Brain Injurymentioning
confidence: 99%
“…Intracranial hemorrhage and midline shift are also indications of increased intracranial pressure. When coupled with vascular compression and secondary cerebral infarction, severe brain edema may occur, which may lead to a significant increase in intracranial pressure (8,25,31). A less severe injury may lead to small-scale single-focal intracranial hematoma associated with less severe postoperative cerebral edema, whereas more traumatic injury often results in multi-focal complex hematoma, which is associated with more severe cerebral edema and increased intracranial pressure (4).…”
Section: Wang X Et Al: Bone Flap Of Traumatic Brain Injurymentioning
confidence: 99%
“…Numerous experimental models have demonstrated that DC reduces secondary brain injury. These effects are thought to be the result of an increase in collateral cerebral circulation, reduction in tissue edema, and improvement in oxygenation and energy metabolism [Stiver, 2009;Weiner et al, 2010]. Furthermore, postoperative radiological evaluation in cases of DC shows amelioration of midline shift, and improvement of the preoperative compression of the basal cisterns [Laalo, et al, 2009].…”
Section: Current Concepts and Controversiesmentioning
confidence: 99%
“…The exact role of other parameters of neuromonitoring, such as brain tissue oxygen, markers of anaerobic metabolism (microdialysis), transcranial Doppler ultrasonography measurements, and electroencephalographic monitoring may provide further information, making the selection of ideal surgical candidate for DC more accurate [Bor-Seng-Shu, et al, 2006;Weiner, et al, 2010]. …”
mentioning
confidence: 99%
“…Aggressive lowering of the blood pressure also decreases absolute PHE growth, at least in patients with volumes of intracerebral hemorrhages of about 10cc [10]. Decompressive craniectomy is a neurosurgical procedure that relieves intracranial pressure; it has been applied in ischemic stroke, cerebral sinus venous thrombosis (CSVT), aneurysmal subarachnoid hemorrhage and traumatic brain injury [23][24][25][26]. Recently, large decompressive craniectomy (DC) without hematoma evacuation showed a trend towards reduced mortality as compared to matched controls [27], and may be a beneficial treatment in selected cases [28].…”
Section: Introductionmentioning
confidence: 99%